Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Satgas Kebersihan Di Dinas Lingkungan Hidup Kabupaten Balangan - Erwin Rizafana (KINDAI, 2020)
Erwin Rizafana Npm.1711.32202.3664, Analysis Of Factors Affecting Performance City Cleanliness Task Force In The Balangan District Environmental Departement, Under The Guidance Of Lanny Purnama Kosasi Dan Yudi Rahman, 2020. The aim of this research is to find out and analyze the influence of individual factors, psychological factors and organizational factors partially on the performance of the Cleanliness Task Force employees, to know and analyze the influence of individual factors, psychological factors and organizational factors simultaneously on employee performance and to find out and analyze among individual factors, psychological factors and organizational factors that have a dominant influence on the performance of the Cleaning Task Force employees at the Balangan District Environmental Office. The population in this study was the cleanliness task force of the Environmental Agency of Balangan Regency with a total of 145 people and the research sample of 31 respondents or 22% of the total population and the method used in the sampling of this study used the census method. This type of data, is an associative research with quantitative paradigms with the application of SPSS and multiple regression analysis. The results of the first hypothesis are known to individual factors, psychological factors and organizational factors partially significant effect on the performance of Cleanliness Task Force employees, the second hypothesis testing is known to individual factors, psychological factors and organizational factors have a significant effect simultaneously on the performance of Cleaning Task Force employees and third hypothesis testing is known that the results of the research that partially tested were stated and proved in this study that psychological factors had a dominant influence on the performance of the Cleaning Task Force employees at the Environmental Service Office of Balangan Regency.Keywords: Individual Factors, Psychological Factors, Organizational Factors And Performance